Differences in the Percentages of Students Enrolled in Dual Credit Courses over Time: A Texas, Multiyear Analysis - Moseley, Stacey M.; Slate, John R. (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This study aimed to determine the degree to which differences were present in the percentages of all students who enrolled in a dual-credit mathematics course in Texas public high schools by their economic status (i.e., economically disadvantaged and all students). The percentages for both groups of students were compared for the 2014-2015 and the 2015-2016 school years. Inferential statistical analyses revealed statistically significant differences in the percentages in dual-credit mathematics course enrollment for all students and students who were economically disadvantaged in both the 2014-2015 and the 2015-2016 school years. For both years, economically disadvantaged students had a lower enrollment rate in dual-credit mathematics courses than all students' percentage enrollment in dual-credit mathematics courses. Implications of these findings, as well as recommendations for future research, were discussed.